EFFECT OF INORGANIC & ORGANIC FERTILIZERS WITH FLY ASH ON MICROBIAL ACTIVITIES OF ACID SOIL UNDER RICE CROP - KIRAN PATEL,; R. N. SINGH, (The Bioscan, 2018)
Field studies were conducted during kharif season of 2014-15 at Ajirma village, Surajpur district(Chhattisgarh), to study the effect of different doses of inorganic & organic fertilizers with fly ash on microbial activities of acid soil under rice crop. The test crop was rice var. MTU-1010 The dehydrogenase activity (DHA) at tillering and harvesting stage of rice soil increased significantly. The highest DHA was recorded in 75% GRD + 40 t fly ash ha-1 + 5 t FYM ha-1 29.63, 28.43µg TPF g-1 soil day-1, while the lowest DHA was observed in control 22.89, 21.40 ug TPF g-1 soil day-1 at tillering and harvesting stage respectively. The similar pattern were observed in both total bacterial count (TBC) and soil microbial biomass carbon (SMBC), that the treatment 75% GRD + 40 t fly ash ha1 + 5 t FYM ha-1 had maximum and the minimum in control, the total bacterial count was 5.60, 4.90 and 4.67, 4.00 x 107 CFU g-1 soil and soil microbial biomass carbon was 128.78, 98.06 and 102.99, 81.21 µg C g-1 dry soil at tillering and harvesting stage respectively.